The Influence of Milling Parameters on Surface Integrity under Different Processing Methods - Wei, Jun (International Journal of Mechanical and Electrical Engineering, 2025)
Ultrasonic assisted milling technology has shown significant effects in improving the quality of machined surfaces, but its specific mechanism of action on the surface and near surface of the workpiece when applied to SLM forming TA15 titanium alloy still needs to be further explored. Under the premise of keeping other cutting conditions constant, as the feed rate of each tooth increases, the machining area covered by the tool expands accordingly, which has a direct impact on the formation of surface microstructure. Based on the above reasons, different microstructures of the machined surface can be obtained by changing the feed rate of each tooth. This article mainly uses surface morphology, roughness, and hardness as key indicators to evaluate the integrity of the machined surface. It systematically analyzes the trend and law of the influence of each tooth feed rate on surface morphology, roughness, and surface hardness during ultrasonic vibration milling of SLM formed TA15 titanium alloy.